Genome-Wide Small RNA Analysis of Soybean Reveals Auxin-Responsive microRNAs that are Differentially Expressed in Response to Salt Stress in Root Apex - Sun, Zhengxi; Wang, Youning; Mou, Fupeng; Tian, Yinping; Chen, Liang; Zhang, Senlei; Jiang, Qiong; Li, Xia (Frontiers in Plant Science, 2016)
Root growth and the architecture of the root system in Arabidopsis are largely determined by root meristematic activity. Legume roots show strong developmental plasticity in response to both abiotic and biotic stimuli, including symbiotic rhizobia. However, a global analysis of gene regulation in the root meristem of soybean plants is lacking. In this study, we performed a global analysis of the small RNA transcriptome of root tips from soybean seedlings grown under normal and salt stress conditions. In total, 71 miRNA candidates, including known and novel variants of 59 miRNA families, were identified. We found 66 salt-responsive miRNAs in the soybean root meristem; among them, 22 are novel miRNAs. Interestingly, we found auxin-responsive cis-elements in the promoters of many salt-responsive miRNAs, implying that these miRNAs may be regulated by auxin and auxin signaling plays a key role in regulating the plasticity of the miRNAome and root development in soybean. A functional analysis of miR399, a salt-responsive miRNA in the root meristem, indicates the crucial role of this miRNA in modulating soybean root developmental plasticity. Our data provide novel insight into the miRNAome-mediated regulatory mechanism in soybean root growth under salt stress.